2008
DOI: 10.1143/jjap.47.5327
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Light Extraction Efficiency in GaN-Based Light Emitting Diodes by Random Pattern of the p-GaN Surface Using a Silica Colloidal Mask

Abstract: A two-dimensional silica colloidal particle was used to etch a p-GaN surface. By treating the p-GaN surface with polyelectrolyte (PE), mono-dispersed silica colloidal particles, 500 nm in diameter, could be uniformly distributed on a 2-in. p-GaN surface. The patterns on the p-GaN surface were produced by a plasma etching process using these colloidal particles as a mask. Etching depths of 150 and 200 nm were produced on the p-GaN surface of LED samples and an increase in the optical output power of 46.7% was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Most recently, several low-cost approaches using selfassembled polystyrene (PS) or/and SiO nanospheres have been employed to improve light extraction efficiency in nitride LEDs [13]- [15]. In this research, we employ a similar method to fabricate large-scale biomimetic surface structures on vertical-injection light-emitting diodes (VI-LEDs).…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, several low-cost approaches using selfassembled polystyrene (PS) or/and SiO nanospheres have been employed to improve light extraction efficiency in nitride LEDs [13]- [15]. In this research, we employ a similar method to fabricate large-scale biomimetic surface structures on vertical-injection light-emitting diodes (VI-LEDs).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the corresponding wall-plug efficiencies (WPE) of conventional LED, LED with PQC on p-GaN surface, LED with PQC on n-side roughing, and LED with PQC structure on p-GaN surface and n-side roughing were 19%, 22%, 24%, and 26%, respectively, which addresses a substantial improvement by the PQC structures on top surface and n-side roughing as well at a driving current of 20 mA. Comparing with the conventional LED, the WPEs of LED with PQC on p-GaN surface, LED with PQC on n-side roughing, and LED with PQC structure on p-GaN surface and n-side roughing were increased by 15.8%, 26.3%, and 36.8%, respectively, at an injection current of 20 mA, The enhancement of WPE of LED with PQC structure on p-GaN surface and n-side roughing is relatively high comparing with other researches [10,13,14,24,25], which is because the light emitted from LED scattered by top PQC pattern and guided onto the LED top direction by n-side roughing [22,23,26], therefore resulting in the enhancement of WPE.…”
Section: Resultsmentioning
confidence: 67%
“…Therefore, a number of studies related to achievement of high light extraction efficiency in LED have been demonstrated by texturing p-GaN surface such as a photonic crystal structure, patterned contact layer, nano-patterned surface, or effective graded-index structures. [2][3][4][5][6][7][8][9] In particular, photonic crystal structures with regular patterns were found to be efficient in enhancing the light extraction efficiency using sophisticated lithography techniques such as e-beam or nano-imprint lithography. 4,5) However, a alternative patterning approach is desirable for further promising applications.…”
mentioning
confidence: 99%
“…By considering the improvement of extraction efficiency without severe degradation of electrical properties of the LEDs, the etching depth of p-GaN was determined to be 150 nm. 8) As a structure of etched p-GaN plane, the distance between ICP-etched plane and quantum well layer is about 100 nm because total thickness of the p-GaN is 250 nm. The lateral-type LED devices of 300 Â 300 m 2 size were fabricated by a normal LED chip process.…”
mentioning
confidence: 99%
See 1 more Smart Citation